The rise of Gig economy - changing nature of unemployment in the developed countries - Burenina, Anastasiia; Hnát, Pavel, 1981-; Brellíková, Miriam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis intends to determine how the gig economy, with online services and paltform, impacts employment structures within developed nations. Developing a gig economy version of employment should help lower international unemployment rates. In addition, it should help bridge the gap between the existing amount of jobs and the skills acquired to be hired. Using quantitative research, case studies, data analysis, and real-world examples from countries such as the United States, United Kingdom, Canada, South Korea, and the European Union. Findings show that although gig employment opens up access to job opportunities for youths and part-time seekers, it fails to provide effective job stability, benefits, or even minimum wage.The thesis concludes that while the gig economy is not an universal solution, with proper regulation and support, it has the potential to play an important role in defining the future of employment. It emphasizes the need for improved protection, fair pay, and appropriate legislation to make gig labor a more viable option.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses